Developmental change of the biorbital angle in normal Japanese infants - Yagasaki T (Dove Medical Press, 2018)
Teiji Yagasaki,1,2 Yoshimi Yokoyama,2 Makiko Tsukui2 1Yagasaki Eye Clinic, Ichinomiya, Aichi, Japan; 2Department of Ophthalmology, Japan Community Health Care Organization Chukyo Hospital, Nagoya, Aichi, Japan Purpose: To investigate postnatal changes in the biorbital angle in normal Japanese children. Subjects and methods: Axial imaging of the orbit in the transverse plane of the horizontal extraocular muscles was obtained in 129 ophthalmologically healthy infants (age ranging from a few months to 11 years). The opening angle between both lateral walls of the orbit was defined as the biorbital angle. Results: The mean biorbital angle in 11 infants less than a year of age was 105.0°±6.0°. The mean biorbital angles for each of the subsequent age groups were 97.7°±3.1°, 96.2°±4.0°, 96.3°±4.1°, 92.8°±3.8°, 92.3°±2.3°, 93.1°±2.8°, 91.5°±3.9°, 91.9°±2.3°, 91.4°±2.3°, and 90.9°±3.1°. The mean biorbital angle in infants less than a year old was significantly larger than those found in the groups of infants older than 1 year (P<0.01, Newman–Keuls test). Conclusion: The biorbital angle in infants less than a year old was larger than that found in infants older than 1 year, with this larger biorbital angle potentially the causative factor of the observed exotropia seen in 70%–80% of newborns gradually disappearing in most cases by 2–4 months of age. Keywords: orbit, computed tomography, magnetic resonance imaging, exotropia, infant